Evaluation of nesting behavior of individual laying hens in an enriched colony housing by using RFID technology - Oliveira, Jofran L.; Xin, Hongwei; Wang, Kailao; Zhao, Yang (International Journal of Agricultural and Biological Engineering, 2019)
The US egg industry is progressively adopting alternative housing systems for laying hens. Provision of nesting places accommodates natural behaviors and may improve the welfare of the laying hen. However, some fundamental questions remain about nesting behaviors of hens under different housing conditions, which would impact system design and management. For instance, how long does a hen use nest per day for egg laying or nest exploration? How many hens nest simultaneously? In such schemes, information on hens’ behavioral and production responses of hens remains relatively sparse. The primary objective of this work was to demonstrate that RFID technology can be used to continuously quantify dynamic nesting behaviors of individual laying hens in a 60-hen enriched colony housing (ECH). Results show that hens spent on average 63.7±1.4 min (mean±SE) in the nest box and made 23.4±0.7 nest visits during a 16 h daily light period. Time spent in and visits to the nest box during the 6 h laying period accounted for 56% and 45% of the light-period value, respectively. Maximum nest occupancy was 29.0%±0.4%. Three distinct phases of egg production in nest boxes were observed: initial (1.5 h), peak (3.2 h, egg laying rate of 0.24±0.01 eggs/min), and late (1.3 h). The majority (95.1%±0.6%) of the daily eggs were laid in the nest box. Considerable variations in nesting behavior among individual hens and day-to-day variations for a given hen were observed. The RFID system will enable researchers to examine the impacts of resource allocations on nesting behaviors of laying hens in alternative hen housing.Keywords: animal welfare, egg production, RFID, alternative hen housing, individual behaviorsDOI: 10.25165/j.ijabe.20191206.5129Citation: Oliveira J L, Xin H W, Wang K L, Zhao Y. Evaluation of nesting behavior of individual laying hens in an enriched colony housing by using RFID technology. Int J Agric & Biol Eng, 2019; 12(6): 7–15.